2005
DOI: 10.1080/03605300500299968
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Fourier Integral Operators with Fold and Blowdown Singularities

Abstract: The purpose of this work is to present results about the composition of Fourier integral operators with certain singularities, for which the composition is not again a Fourier integral operator. The singularities considered here are folds and blowdowns. We prove that for such operators, the Schwartz kernel of F * F belongs to a class of distributions associated to two cleanly intersection Lagrangians. Such Fourier integral operators appear in integral geometry, inverse acoustic scattering theory and Synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(78 citation statements)
references
References 21 publications
1
77
0
Order By: Relevance
“…In this case, we show that both projections π L and π R have singularities called blowdowns (see section 2). Such canonical relations were studied before in [12] and in [7], [4] (where only one projection has blowdown singularities).…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, we show that both projections π L and π R have singularities called blowdowns (see section 2). Such canonical relations were studied before in [12] and in [7], [4] (where only one projection has blowdown singularities).…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…We can find the strength of the artifacts by finding the order of F * F on Λ \ ∆. It is shown in section 3 that these artifacts are stronger (case 2) or have equal strength with ∆ (cases 3,4).…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…In the case of the single source model, with only fold caustics appearing, Nolan [25] showed that F is an FIO associated to a folding canonical relation in the sense of [21] (also called a two-sided fold), and stated that the Schwartz kernel of the operator F * F belongs to a class of distributions associated to two cleanly intersecting Lagrangians in (T * Y \ 0) × (T * Y \ 0). This was fully proved in [5]. The corresponding canonical relations are the diagonal ∆ and a folding canonical relation, different from the original one, which lies in T * X × T * Y .…”
Section: Introductionmentioning
confidence: 98%
“…Following an idea from [12], [5], we now make a singular change of variables, T : R n → R n−1 , T (θ ′′ , z n−1 , z n ) = (ξ ′′ , ξ n−1 ), given by:…”
Section: C0mentioning
confidence: 99%
See 1 more Smart Citation